A Novel Tannic Acid-Based Carbon-Supported Cobalt Catalyst for Transfer Hydrogenation of Biomass Derived Ethyl Levulinate - Wang, Meng; Yao, Xuefeng; Chen, Yuxin; Lin, Baodong; Li, Na; Zhi, Keduan; Liu, Quansheng; Zhou, Huacong (Frontiers in Chemistry, 2022)
The catalytic conversion of ethyl levulinate (EL) to γ-valerolactone (GVL) is an important intermediate reaction in the conversion and utilization of biomass resources. The development of novel and efficient catalysts is significantly important for this reaction. In this work, using the biomass-derived tannic acid as carbon precursor and the transition metal cobalt as active component, a novel tannic acid carbon supported cobalt catalyst (Co/TAC) was prepared by pyrolysis and subsequent hydrazine hydrate reduction method. The hydrogenation of EL and other carbonyl compounds by hydrogen transfer reaction was used to evaluate the performance of the catalysts. The effects of different preparation and reaction conditions on the performance of the catalysts were investigated, and the structures of the prepared catalysts were characterized in detail. The results showed that the carbonization temperature of the support had a significant effect on the activity of the catalyst for the reaction. Under the optimized conditions, the Co/TAC-900 catalyst obtained the highest GVL yield of 91.3% under relatively mild reaction conditions. Furthermore, the prepared catalyst also showed high efficiency for the hydrogenation of various ketone compounds with different structures. This work provides a new reference for the construction of the catalysts during the conversion of biomass and a potential pathway for the high-value utilization of tannin resource.